Deposition of indium nitride films by activated reactive evaporation process - a feasibility study - Patil, Sheetal J.; Bodas, Dhananjay S.; Mandale, A. B.; Gangal, S. A. (Applied Surface Science, 2005)
Indium nitride (InN) films are deposited by `activated reactive evaporation (ARE)' process using parallel plate coupled nitrogen plasma (radio frequency source of 13.56 MHz) and evaporation of pure indium powder by resistive heating. Depositions are carried out by varying RF plasma power, on n-type silicon &LANGBRAC; 1 0 0&RANGBRAC; substrate, maintained at room temperature, at a nitrogen gas pressure of 1.06 x 10(-1) Pa (8 x 10 (-4) Torr). The film's crystallinity was examined by X-ray diffraction (XRD) and topography by scanning electron microscope (SEM). The diffraction pattern shows polycrystalline nature of the deposited films with characteristics of hexagonal structure. XRD peak intensity increases with increase in power. SEM observations show a smooth and pinhole free surface having improved quality of film with hexagonal structure as the power is increased from 60 to 120 W. Primary X-ray photoelectron spectroscopy (XPS) results show binding energies of the In 3d levels and N 1s level matching well with that of stoichiometric InN. Further, the refractive index of the films, measured by ellipsometry, is in the range of η = 2.79-2.91 with the variation of plasma power, which is in good agreement with the standard value for indium nitride (η = 2.9). These results indicate the feasibility of using, `activated reactive evaporation (ARE)' process for indium nitride depositions on silicon &LANGBRAC; 1 0 0&RANGBRAC; substrates maintained at room temperature. © 2004 Elsevier B.V. All rights reserved.
Keywords: activated reactive evaporation; ellipsometry; indium nitride; SEM; XRD

Deposition of PTFE thin films by RF plasma sputtering on < 100 > silicon substrates - Bodas, Dhananjay S.; Mandale, A. B.; Gangal, S. A. (Applied Surface Science, 2005)
Polymers have been studied extensively due to the wonderful array of properties presented by them. Polymer materials can be coated/deposited by various techniques like sputtering (magnetron, ion beam, RF or dc), plasma polymerization, etc. and can be used in coatings, paint industries, etc. The present study deals with the RF sputter deposition of poly(tetrafluoro ethylene) (PTFE), commonly known as Teflon. Depositions were carried out on mirror polished silicon (1 0 0) substrates at different powers in the range of 100-200 W. The deposition time was kept constant at 60 min. The sputtered film shows lower contact angle of 50&DEG; with water and 44&DEG; with diiodomethane, a lower interfacial tension value of 0.76 dyne/cm, indicating hydrophilicity and good adhesion of the film with the substrate. FHR indicates presence of C-F, C-F-2 bonding groups in the deposited film. Further, XPS study shows presence of CF3 (292.2 eV), CF2 (290.8 eV), C-F (288.0 eV) and C-CF (286.4 eV) moieties indicating deposition of PTFE films at higher power levels of plasma. © 2004 Elsevier B.V. All rights reserved.
Keywords: Contact angle measurement; FTIR; PTFE; RF plasma sputtering; XPS

Electron beam induced surface cross-linking of functional monomers coated on silicon substrate - Mahapatra, S. K.; Bodas, Dhananjay S.; Mandale, A. B.; Gangal, S. A.; Bhoraskar, Vasant N. (Materials Letters, 2006)
A 3: 1 composition of functional monomer: multifunctional acrylate was spin coated and later cross-linked under the influence of keV electron irradiation on the surface of silicon to generate a surface-anchored cross-linked network bearing functional moieties. Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM) as well as wetting angle measurements were used for the analysis of functional monomer cross-linked surfaces. Results of the surface reconstruction of surfaces and electron irradiated on coated silicon wafers reveal that long-term hydrophilic surfaces can be achieved. Thus, the surface architecture can be favorably manipulated by using this remarkable technique with a Suitable combination of functional monomers and cross-linkers. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: electron beam irradiation; FTIR; Polymers; surface modification; XPS

Quantum dot based immunosensor using 3D circular microchannels fabricated in PDMS - Morarka, Amit; Agrawal, Shailaja; Kale, Sonia; Kale, Anup; Ogale, Satishchandra B.; Paknikar, Kishore; Bodas, Dhananjay S. (Biosensors & Bioelectronics, 2011)
Microchannel is basic functional component of microfluidic chip and every step-forward of its construction technique has been receiving concern all over the world. The present work describes a novel, rapid and simple fabrication technique for building 3D microchannels in poly(dimethyl siloxane) (PDMS) elastomer. These microchannels were used for rapid detection of antigens (E. coli) by quantum dot (QD) based approach. Luminescent QD (CdTe) were synthesized by aqueous method and characterized using high resolution transmission electron microscopy (HRTEM), fluorescence spectroscopy and X-ray diffraction (XRD). The QDs were functionalized with anti-E. coli antibodies for immuno-detection. The reported process allowed easier and faster method of fabrication of circular 3D micochannels and demonstrated their potential use in an immuno-biosensor device. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Capillary driven flows; Circular microfluidics; Immunosensor; QDs

Surface studies on benzophenone doped PDMS microstructures fabricated using KrF excimer laser direct write lithography - Kant, Madhushree Bute; Shinde, Shashikant D.; Bodas, Dhananjay S.; Patil, K. R.; Sathe, V. G.; Adhi, K. P.; Gosavi, S. W. (Applied Surface Science, 2014)
his paper discusses microfabrication process for benzophenone doped polydimethylsiloxane (PDMS) using laser lithography. KrF excimer laser of 248 nm with 20 ns pulse width at repetition rate of 1 Hz was used for microfabrication of undoped and benzophenone doped PDMS. The doped-PDMS shows sensitivity below 365 nm, permitting processing under ambient light. The analysis of etch depth revealed that doped PDMS shows self developable sensitivity at lower fluence of similar to 250 mJ/cm(2). The unexposed and exposed surface was studied using Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy and Scanning electron microscopy (SEM). Spectrocopic analysis indicated increase in C-O, C=O, Si-O-3 and Si-O-4 bonding at the expense of Si-C and Si-O-2 bonds of PDMS. In case of laser exposed doped-PDMS, removal of benzophenone from probe depth of spectroscopy was observed. Whereas the surface morphology of exposed and unexposed doped-PDMS was observed to be same, indicating clean development of PDMS micropattems. The present study indicates that addition of 3.0 wt.% benzophenone in PDMS enhance self development sensitivity of PDMS. The self developable results on doped-PDMS are quite encouraging for its potential use in point of care Lab-On-Chip applications, for fabricating micropattems using direct write laser lithography technology.
Keywords: Direct write laser lithography; Microfabrication; micropatterning; Poly(dimethylsiloxane) (PDMS)

Hydrothermal synthesis and characterization of carbon nanospheres: a mechanistic insight - Bhagat, P. N.; Patil, K. R.; Bodas, Dhananjay S.; Paknikar, K. M. (RSC Advances, 2015)
Hydrothermally synthesized carbon nanospheres (CNS) follow a process of early nucleation followed by growth during synthesis. Here we report that growth occurs precisely after 5 min and prior to it nucleation occurs. The nucleation is a brief step in nanoparticle formation followed by growth of the nanoparticle depending on the reaction parameters.